Multifocal ERG recordings under visual control of the stimulated fundus in mice - Dutescu, Ralf M.; Skosyrski, Sergej; Kociok, Norbert; Semkova, Irina; Mergler, Stefan; Atorf, Jenny; Joussen, Antonia M.; Strauss, Olaf; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2013)
Therapeutic approaches to retinal disease require a continuous monitoring of functional improvement over lesion areas that sometimes cannot be shown in full-field ERG. The aim of this study was to assess the usefulness of multifocal electroretinograms (mfERGs) under visual control using scanning laser ophthalmoscopy (SLO) for evaluation of local retinopathy in mice.mfERGs were optimized for recordings in C57BL/6 mice by varying dark steps between each stimuli, background intensity, and the numbers of hexagons. Local retinopathy was induced by argon laser photocoagulation with different spot sizes and retinal irradiances. mfERG recordings were performed before, and 10 days and 4 weeks after laser treatment. In each recording, the central hexagon was positioned on the optic nerve head visualized by SLO images. The amplitudes of the P1 response components were analyzed as a function of retinal location.The mfERG amplitudes depended on stimulus condition. The P1 amplitudes increased with increasing number of dark frames in the m-sequence and with decreasing number of hexagons. A stimulus with 19 hexagons and four dark frames was chosen because substantial response amplitudes could be achieved while preserving sufficient spatial resolution. In the untreated eyes, the response to the central hexagon, stimulating the optic nerve head, was smaller than those to the surrounding hexagons. The responses to hexagons stimulating photocoagulated areas were reduced compared with the responses of surrounding areas. The amplitude reduction was more pronounced when the coagulated areas were larger and when higher energies were used.Areas with decreased sensitivities to light stimulation (either the optic nerve head or damaged retinal areas) can be detected and correlated with the retinal images and in the mfERG responses. We demonstrate that the mfERG technique is able to reproducibly detect the functional consequences of a local treatment.
EVALuna2:21138